Evaluation of distance education and alternating education to confront the corona of morocco during the two years 2020. 2021 pros negatives - Achandir, Mohamed (Journal of Educational and Psychological Sciences, 2022)
This research aims to stand on distance education and compare it with rotational education in light of the corona pandemic in the kingdom of Morocco, it also aims to stand on the tremendous efforts made by the kingdom of morocco in improving these two types of education. The research included four topics: the first topic is the reality of distance education in the official documents of the kingdom of morocco. The second topic included alternating education as an alternative solution to distance education. As for the third topic, it compared between distance education and alternating education. And the fourth and final topic, in which l mentioned the efforts of the kingdom of morocco in making education successful in the time of corona. In the end, l concluded many results, including: Education about some was only applied in the corona pandemic, and if it was found before that in official documents, both distance education and alternating education contained pros and cons, the kingdom of morocco made various efforts to make education successful in the time of corona. Based on the previous results, l recommend researchers to conduct a field study of educational institutions in order to determine the results obtained during distance education and alternating education to find out the success of this type of education.
Keywords: distance Learning; alternate education; The Kingdom of Morocco; negative results